75.4k views
3 votes
Solve for c.



3abc + b = 5

c =
c = 2 - ab
c = -

User Joelmc
by
4.6k points

2 Answers

3 votes

Answer: -b-5/3ab

Explanation:

3abc + b = 5

3abc + b - b = 5 - b

3abc = 5 - b

3abc / 3ab = (5 - b) / 3ab

c = (5 - b) / 3ab

User Mark Dolbyrev
by
5.3k points
2 votes

Answer:

c =
(5-b)/(3ab)

Explanation:

Given

3abc + b = 5 ( isolate the term in c by subtracting b from both sides )

3abc = 5 - b ( divide both sides by 3ab )

c =
(5-b)/(3ab)

User Valenzio
by
4.6k points